"There Is Zero Regulation on the Selling of Alcohol": The Voice of the Youth on the Context and Determinants of Alcohol Drinking in Lebanon. (April 2018) - Yassin, Nasser; Afifi, Rima; Singh, Neil; Saad, Reem; Ghandour, Lilian
Alcohol-related research from the Arab world has rarely touched on the experiences or views of Arab adolescents. In this article, we present an in-depth analysis of youth alcohol drinking patterns and determinants derived from focus group discussions completed with more than 100 Lebanese high school/vocational students (15–19 years). The social ecology of alcohol use framework guided our research and analysis. Findings reveal that alcohol drinking is perceived as a pervasive and serious public health problem, triggered by a complex web of social relations, and facilitated by lax policies. Recommendations to curb heavy/harmful alcohol drinking among adolescents include regulating the role of alcohol industry, providing alternative recreational spaces/pass-times, educating about alcohol-related harms, and promoting more research on alcohol and its harms. Findings confirm the social ecology of alcohol use framework, and suggest the addition of the macro level of influence to this model, namely, a comprehensive alcohol harm reduction policy.